2019
DOI: 10.5624/isd.2019.49.3.209
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of morphometric features of fossa navicularis using cone-beam computed tomography in a Turkish subpopulation

Abstract: PurposeFossa navicularis is a bone defect in the clivus. Familiarity with this anatomical variant is important because it is close to vital anatomical structures in the base of the skull. The aim of this study was to determine the prevalence and morphometric properties of fossa navicularis within the clivus in a Turkish subpopulation using cone-beam computed tomography (CBCT).Materials and MethodsA total of 168 CBCT scans (female: 96, male: 71) were evaluated. High-quality CBCT images of patients without a syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
1
8
1
Order By: Relevance
“…Cankal et al 25 reported frequencies of 5.3% (26 of 492 dry skulls) and 3% (16 of 525 CT images). However, Bayrak et al, 1 Ersan, 3 Kaplan et al, 26 and Magat 27 all reported higher frequencies than in the current study: 7.6, 6.6, 17.4, and 27.5%, respectively.…”
Section: Discussioncontrasting
confidence: 67%
“…Cankal et al 25 reported frequencies of 5.3% (26 of 492 dry skulls) and 3% (16 of 525 CT images). However, Bayrak et al, 1 Ersan, 3 Kaplan et al, 26 and Magat 27 all reported higher frequencies than in the current study: 7.6, 6.6, 17.4, and 27.5%, respectively.…”
Section: Discussioncontrasting
confidence: 67%
“…The average depth, length, and width were 2.22 mm, 8.5 mm, and 5.37 mm, respectively. No sex predisposition for the presence of an FNM was reported; however, a positive correlation between patient age and length of the FNM was noted 22 . In a more extensive study of 723 CBCT scans, the prevalence of FNM was 6.6% and a predominance among males was reported.…”
Section: Discussionmentioning
confidence: 94%
“…Cankal and colleagues 15 presented separate analyses of dry skulls and imaging studies, and found FNM in 5.3% of dry skulls, but only in 3% of CT scans. However, Magat 5 presented an outlier study with an incredible reported 27.5% prevalence of FNM variations on CT scans. Their article mentioned the substantial difference from previous studies and related the change to differences in methodologies, ethnicities, and sample size.…”
Section: Resultsmentioning
confidence: 99%
“…The ranges of dimensions of FNM varied as well, with the mean diameter ranging from 2.85 to 5.37 mm, the mean length ranging from 5.12 to 8.55 mm, and the mean depth being approximately 2.2 mm in all 3 studies. 5 15 16 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation